Análisis de los determinantes de las asignaciones salariales entre hombres y mujeres en la industria manufacturera en Bogotá 2016-2019. (2022)
The manufacturing industry in Bogotá is one of the sectors that has the highest demand for labor and with it production and wages. Its human capital confirmed by men and women constitutes its production base. With the legislative reforms and the flexibility of the labor market, it allowed for a greater demand for labor and also a greater supply was generated, made up of total sales, which allows it to be sustainable over time. Although in the production function wages are part of the work factor, this is assigned by employers according to how much each hired staff produces and this makes possible the growth of the industry in Bogotá. The research focuses on knowing the determinants of wages in the manufacturing industry, which were analyzed through descriptive statistics and cross-sectional econometrics.